3D star shot analysis using MAGAT gel dosimeter for integrated imaging and radiation isocenter verification of MR‐Linac system. Issue 6 (18th April 2022) - Kim, Jeong Ho; Kim, Bitbyeol; Shin, Wook‐Geun; Son, Jaeman; Choi, Chang Heon; Park, Jong Min; Hwang, Ui‐Jung; Kim, Jung‐in; Jung, Seongmoon
Abstract: Purpose: This study aims to investigate a star shot analysis using a three‐dimensional (3D) gel dosimeter for the imaging and radiation isocenter verification of a magnetic resonance linear accelerator (MR‐Linac). Methods: A mixture of methacrylic acid, gelatin, and tetrakis (hydroxymethyl) phosphonium chloride, called MAGAT gel, was fabricated. One MAGAT gel for each Linac and MR‐Linac was irradiated under six gantry angles. A 6 MV photon beam of Linac and a 6 MV flattening filter free beam of MR‐Linac were delivered to two MAGAT gels and EBT3 films. MR images were acquired by MR‐Linac with a clinical sequence (i.e., TrueFISP). The 3D star shot analysis for seven consecutive slices of the MR images with TrueFISP was performed. The 2D star shot analysis for the central plane of the gel was compared to the results from the EBT3 films. The radius of isocircle (ICr ) and the distance between the center of the circle and the center marked on the image (ICd ) were evaluated. Results: For MR‐Linac with MAGAT gel measurements, ICd at the central plane was 0.46 mm for TrueFISP. Compared to EBT3 film measurements, the differences in ICd and ICr for both Linac and MR‐Linac were within 0.11 and 0.13 mm, respectively. For the 3D analysis, seven consecutive slices of TrueFISP images were analyzed and the maximum radii of isocircles (ICr_max ) were 0.18 mm for Linac and 0.73 mm for MR‐Linac. The tilting angles of radiation axis were 0.31° for Linac and 0.10° for MR‐Linac. Conclusion: The accuracy of 3D star shot analysis using MAGAT gel was comparable to that of EBT3 film, having a capability for integrated analysis for imaging isocenter and radiation isocenter. 3D star shot analysis using MAGAT gel can provide 3D information of radiation isocenter, suggesting a quantitative extent of gantry‐tilting.